Renaissance cultural crossroads - Barker, Sara,Hosington, Brenda (Brill, 2013)
The role of translations and translators in the production of English incunabula / Brenda M. Hosington – Lydgate's Fall of princes : translation, re-translation and history / A.S.G. Edwards – Reading Juan de Flores's Grisel y Mirabella in early modern England / Joyce Boro – Learning style from the Spaniards in sixteenth-century England / Barry Taylor – Print, paratext, and a seventeenth century sammelband : Boccaccio's Ninfale Fiesolano in English translation / Guyda Armstrong – Versifying philosophy : Thomas Blundeville's Plutarch / Robert Cummings – War, what is it good for? : sixteenth-century english translations of the – Classics / Fred Schurink – Cato in England : translating Latin sayings for moral and linguistic instruction / Demmy Verbeke – John Hester's translations of Leonardo Fioravanti : the literary career of a London distiller / Isabelle Pantin – 'For the common good and for the national interest' : paratexts in English translations of navigational works / Susanna De Schepper – Henry Hexham (c.1585-1650), English soldier, author, translator, lexicographer, and cultural mediator in the Low Countries / Paul Hoftijzer – 'Newes lately come' : European news books in English translation / S.K. Barker
Includes bibliographical references and index
Keywords: Literature; Translating and interpreting; Book industries and trade; Translations; Early printed books; Incunabula; Language and culture; Books and reading